PENGARUH EKSTRAK JAHE (Zingiber officinale Rosc.) TERHADAP KADAR HALITOSIS PENGGUNA GIGI TIRUAN LENGKAP RESIN AKRILIK - , NIKITA IKA SARI; , drg. Endang Wahyuningtyas, M.S., Sp.Pros.(K) ([Yogyakarta] : Universitas Gadjah Mada, 2013)
In aging process, problems such as dry mouth and loss of teeth need treatment, for example by using full dentures. Full dentures usage especially with acrylic-base can cause halitosis. It is caused by some factors such as food leftovers that sticks to the denture surfaces and the presence of bacteria and fungi in the mouth. The main causes of halitosis are Volatile Sulfur Compounds (VSC), which consists of H2S, CH3SH, and CH3SCH3. Ginger (Zingiber officinale Rosc.) is a traditional plant that has many benefits. Ginger can be made in the form of extract, powder, or gel as needed. Ginger has active substances such as volatile oil and gingerol which are served as effective antibacterial and antifungal. The aim of this study was to determine the effect of ginger extract with 10 % concentration on halitosis levels in full denture wearers. Twenty denture wearersâ levels of halitosis are being measured by a machine called oral chroma before and after their dentures are being immersed in water (as control) and ginger extract with 10% concentration for 8 hours. Data consisted of H2S, CH3SH, and CH3SCH3 then calculated by Independent t-test with a confidence level of 95%. The results showed a significant difference between group 1 (denture wearersâ levels of halitosis after their dentures immersed in water) and group 2 (denture wearersâ levels of halitosis after their dentures immersed in ginger extract with 10% concentration). Significant differences indicated by decreased levels of H2S, CH3SH, dan CH3SCH3. The conclusion of this study is that ginger extract (Zingiber officinale Rosc.) with 10% concentration can reduce the full denture wearersâ levels of halitosis. The highest level of reduction has been shown by Hydrogen Sulfide (H2S).